Wide-ranging survey on the laminar flow of individual Taylor bubbles rising through stagnant Newtonian liquids - J. D. P. Araújo (2012)
A wide-ranging numerical survey of the rising of individual Taylor bubbles through vertical columns of stagnant Newtonian liquid in laminar flow regime is presented in the present paper. The CFD procedure applied is based in the volume of fluid (VOF) methodology of the commercial package Ansys FLUENT. The simulations performed covered wide ranges of column diameters and viscosities, corresponding to Morton and Eotvos numbers within the intervals of 4.72 x 10(-5) to 104 and 6-900, respectively. Several relevant hydrodynamic features regarding the three main flow regions considered (nose region, liquid film and wake region) were determined. In some cases, these features were favourably compared to predictions of available correlations and theoretical equations. Due to the lack of published material about the wake structure, a particular interest was taken on this flow region, where some general equations are presented to estimate the related hydrodynamic features. This study can become a useful tool for future studies on slug flow systems.